PEMODELAN PIFTICY THEORY (SPIRIT OF SELF TENACITY AND EFFICACY THEORY) DAN DAMPAKNYA TERHADAP KINERJA PERSONAL DENGAN SA-CILUS THEORY (STAR ASSURANCE BASED SOCIAL STATUS THEORY) SEBAGAI VARIABEL MEDIASI: Studi pada Dosen PTS di Kota Palembang - Eka Muzalfitri Ridwan (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2018)
The role and the function of a lecturer in a private college is very crucial in accordance with a lecturer can serve some college students in the shape of scientific education, knowledge, science, and even new technologies. So, in this matter how hard a lecturer’s job to fulfill and satisfy the students’ skill and education until they can get their hope like academic degrees. The classical problems that researcher finds not only from the research gap but also from empirical studies found that lecturers’ prosperities and their recognitions of their skill and expert and even scientific researches are very apprehensive until their motivation at work is low, not loyal to the job, unsatisfied, and even overloading job without any recognitions from their foundation or institution. This research has found that PIFTICY theory and SA-CILUS theory are successfully generated as new theories or postulates to contribute science addition and development in human resource management and organizational behavior until problems in personal performance in this research can be solved. the method of this research using AMOS programme that results PIFTICY significantly influences on personal performance with the grade of 0,963 and SA-CILUS as a mediating variables that influences on PIFTICY with the grade of 0,045. Not only the grand theoretical model in this resaerch is proper but also empirical model in this research can be proper and accepted as a new-research construct.